2000
DOI: 10.1108/02656710010315247
|View full text |Cite
|
Sign up to set email alerts
|

An instrument for measuring TQM implementation for Chinese manufacturing companies

Abstract: Access to this document was granted through an Emerald subscription provided by University of Calgary For Authors:If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service. Information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comWith over forty years' experience, Emerald Group Publishing is a le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
291
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(304 citation statements)
references
References 21 publications
6
291
0
7
Order By: Relevance
“…This suggests that training and educational programs in the firms help to enhance their employee's knowledge, skills and behaviors which ultimately improve the quality of products and services. This findings support the previous empirical studies that have found training and education as a critical factor for the successful quality improvement implementation in organization (Thiagarajan and Zairi, 1997;Quazi and Padibjo, 1998;Yusof and Aspinwall, 1999;Zhang et al, 2000;Calisir et al, 2001;Dayton, 2001;Pun, 2001). Finally, reward and recognition also was found to have significant positive contributions towards quality improvement in the sampled firms.…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that training and educational programs in the firms help to enhance their employee's knowledge, skills and behaviors which ultimately improve the quality of products and services. This findings support the previous empirical studies that have found training and education as a critical factor for the successful quality improvement implementation in organization (Thiagarajan and Zairi, 1997;Quazi and Padibjo, 1998;Yusof and Aspinwall, 1999;Zhang et al, 2000;Calisir et al, 2001;Dayton, 2001;Pun, 2001). Finally, reward and recognition also was found to have significant positive contributions towards quality improvement in the sampled firms.…”
Section: Discussionsupporting
confidence: 90%
“…Customer focus and training & education are measured by a five-item scale and ranges from (1) "strongly disagree" to (5) "strongly agree" developed by Zhang (1999). Teamwork is measured by using four-point Likert scale developed by Flynn et al (1994) and Lau and Idris (2001).…”
Section: Instrumentationmentioning
confidence: 99%
“…Similarly, McAdam and Kelly (2002) supported the claim by confirming that training and development are important elements in TQM activities. Moreover, Zhang et al (2000) demonstrated that firms believe that education and training form a significant part of all TQM initiatives.…”
Section: Education and Training And Quality Culturementioning
confidence: 99%
“…Its focus is on adherence to quality and it ensures that process capability is able to bring about the production needs (Zhang et al, 2000). Similarly, Oakland (1993) revealed that process management is a process of convincing employees that they are responsible for their work in terms of customer satisfaction and Motwani (2001) contended that process management adds value to a process, maximizes each employee's productivity and enhances the quality of the firm.…”
Section: Process Management and Quality Culturementioning
confidence: 99%